RELATIONSHIP BETWEEN DENTAL VISIT TOWARDS QUALITY OF LIFE IN PRIMARY HEALTH CITEREUP CIMAHI - Asri Lestari, Ayu; Belva S, Almira; Khaitunnisa, Khansa; Widjaja, Aisyah (Journal of Health and Dental Sciences, 2025)
The aim of this study was to determine the relationship between Oral Health Quality of Life (OHRQoL) and the number of visits to the dentist. This is a cross-sectional study. This study using OHIP questionnaire and additional question about healthcare insurance ownership. Data were analysis using SPSS version 25. The findings of a study including 62 respondents. The prevalence respondent on 44-60 years old were 38,7%. Most of them as BPJS ownership and as unemployment. The highest prevalence OHRQOL based on dental utilization were low categorize and more than 6 months dental visit. The result bivariate analytic and statistically of Pearson chi square test, there are differences between OHRQol categorize towards dental visit p=0,000. Correlation between OHRQoL with dental visit statistically significant p=0,000 r=0,606. Maintaining dental and oral health by providing promotive and preventive programs can reduce the prevalence of visits to the dentist and can improve quality of life status. There are several determinant factors affected towards dental utilization. Universal health coverage is one of determinant factors to prevent out of pocket expenditures. DOI : 10.54052/jhds.v4n3.p247-254